Progress in Location-Based Services 2014 - Gartner, Georg; Huang, Haosheng (Springer, 2015)
This book presents a general picture of recent research activities related to location-based services. Such activities emerged in the last years especially concerning issues of outdoor/indoor positioning, smart environment, spatial modelling, personalization and context-awareness, cartographic communication, novel user interfaces, crowdsourcing, social media, big data analysis, usability and privacy. This book is comprised of a selection of the best papers presented during the 11th International Symposium on Location Based Services, which was held in Vienna (Austria) between 26th and 28th November 2014